1998
DOI: 10.1046/j.1365-2443.1998.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

The proteasome: a protein‐destroying machine

Abstract: Most cellular proteins are targeted for degradation by the proteasome, a eukaryotic ATPdependent protease, after they have been covalently attached to ubiquitin (Ub) in the form of a poly Ub chain functioning as a degradation signal. The proteasome is an unusually large multisubunit proteolytic complex, consisting of a central catalytic machine (called the 20S proteasome) and two terminal regulatory subcomplexes, termed PA700 or PA28, that are attached to both ends of the central portion in opposite orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
74
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 74 publications
(100 reference statements)
1
74
0
4
Order By: Relevance
“…Many proteins with a structural similarity to ubiquitin present in cells, Ubls (ubiquitin-like proteins), are divided into two subclasses: small, type-1 Ubls, such as SUMO-1 and NEDD8, that are ligated to target proteins in a similar manner to ubiquitin, and type-2 Ubls containing ubiquitin-like structures within a variety of large proteins having distinct functions, such as Elongin B, Rad23, and Parkin. Although ubiquitin and type-1 Ubls are central players in post-translational protein modification, the significance of type-2 Ubls remains obscure (42,43). The lack of a diglycine motif at the C-terminal end of the ubiquitin domain suggests that Herp is a type-2 Ubl.…”
Section: Discussionmentioning
confidence: 99%
“…Many proteins with a structural similarity to ubiquitin present in cells, Ubls (ubiquitin-like proteins), are divided into two subclasses: small, type-1 Ubls, such as SUMO-1 and NEDD8, that are ligated to target proteins in a similar manner to ubiquitin, and type-2 Ubls containing ubiquitin-like structures within a variety of large proteins having distinct functions, such as Elongin B, Rad23, and Parkin. Although ubiquitin and type-1 Ubls are central players in post-translational protein modification, the significance of type-2 Ubls remains obscure (42,43). The lack of a diglycine motif at the C-terminal end of the ubiquitin domain suggests that Herp is a type-2 Ubl.…”
Section: Discussionmentioning
confidence: 99%
“…Other candidates that may interact with PCNA are proteins associated with the ubiquitin-proteasome pathway (50). Proteasome was originally described as a holoenzyme playing an important role in the production of peptides presented by MHC class I molecules (50), but recent studies have revealed proteasome to be involved in cell cycle regulation and to bind to cyclin B, cyclin D, p21, CDK 5, and p27, all of which interact with PCNA (50 -53).…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination was originally characterized as a signal for protein destruction by the proteasome (1). However, recent developments have implicated ubiquitin in control of a multitude of cellular processes including signal transduction, apoptosis, DNA repair, protein-protein interaction, endocytosis, and protein trafficking (2)(3)(4).…”
mentioning
confidence: 99%